Studying the Changes of Time to Stabilization and Center of Pressure Velocity in Athletes with an Unilateral Isolated Anterior Cruciate Ligament Rupture in a Six-Month Follow-Up - Rahbari, Afshin; Rahimi, Abbas; Khademi Kalantari, Khosro; Akbarzadeh Baghaban, Alireza; Shavehee, Yaghoob (Journal of Clinical Physiotherapy Research, 2021)
Introduction: Anterior cruciate ligament rupture has shown vast changes in kinematics and kinetics parameters of lower limbs. The aim of this study was to investigate the balance changes including time to stabilization (TTS) and velocity of the center of pressure (CoP) displacement in professional male and female athletes aged between 20 and 40 years. Methods and Materials: The present cohort study was conducted on 58 male and female professional athletes (mean age: 26.9). The individuals were divided into two healthy and ACL-deficient knee groups, each with 29 people. The TTS and velocity of CoP displacement in both anterior-posterior and medial-lateral directions were calculated in the forward jumping test on a force platform. The test was performed three times consisted on the end of the 2nd, 4th and 6th months post injury. Based on the type of data distribution, either Repeated Measures or Friedman test was used to evaluate within-group changes over time, and an Independent or Mann-Whitney test was utilized to compare between-group changes. Results: The results showed significant difference between the healthy and ACL-D groups in TTS and CoP velocity. The TTS was different between groups (P=0.494 for 2nd, P=0.008 for 4th, and P=0.041 for 6th month post injury). The CoP velocity in AP direction showed no significant difference between groups (P=0.419 for 2nd, P=0.196 for 4th, and P=0.36 for 6th month after injury). However, there was a significant difference between groups in 4th month post injury (P=0.359 for 2nd, P=0.01 for 4th, and P=0.331 for 6th post injury) in ML direction. Conclusion: Considering all parameters, it seems that improvement was occurred between 2nd and 4th months but not between 4th and 6th months. It can be said that most of the changes of TTS and CoP occur in the first months after the injury.